2005
DOI: 10.1530/rep.1.00625
|View full text |Cite
|
Sign up to set email alerts
|

The role of progesterone in endometrial angiogenesis in pregnant and ovariectomised mice

Abstract: The role of progesterone (and oestrogen) in endometrial angiogenesis remains controversial. The aims of this study were to quantify endometrial angiogenesis in pregnant mice and to investigate the role of progesterone in promoting endothelial cell proliferation in ovariectomized mice. Uteri were collected on days 1 to 4 of pregnancy when circulating progesterone concentrations were increasing, prior to implantation. Before dissection, mice were injected with bromodeoxyuridine (BrdU) enabling proliferating endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 35 publications
8
84
0
Order By: Relevance
“…Few studies have quantified endothelial cell proliferation in mouse uterus; however, our data are consistent with those previously published that have used a similar methodology. The number of PEC observed at 24 h in the current study is within the range observed in our previous studies of mouse endometrium during early pregnancy (days 1 and 2: no PEC; day 3: 142.3 PEC/mm 2 (2.3-219.4); day 4: 129.0 PEC/mm 2 (34.0-272.6)), after 3 days of progesterone treatment (97.3 PEC/mm 2 (60.8-203.4)), or 24 h following E 2 treatment (179.2 PEC/mm 2 (10.5-307.8)) (Walter et al 2005). While these data demonstrate that endothelial cell proliferation occurs in the endometrium under different hormonal conditions, they do not illustrate whether a specific vessel population is affected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have quantified endothelial cell proliferation in mouse uterus; however, our data are consistent with those previously published that have used a similar methodology. The number of PEC observed at 24 h in the current study is within the range observed in our previous studies of mouse endometrium during early pregnancy (days 1 and 2: no PEC; day 3: 142.3 PEC/mm 2 (2.3-219.4); day 4: 129.0 PEC/mm 2 (34.0-272.6)), after 3 days of progesterone treatment (97.3 PEC/mm 2 (60.8-203.4)), or 24 h following E 2 treatment (179.2 PEC/mm 2 (10.5-307.8)) (Walter et al 2005). While these data demonstrate that endothelial cell proliferation occurs in the endometrium under different hormonal conditions, they do not illustrate whether a specific vessel population is affected.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model was adapted from previous studies (Heryanto & Rogers 2002, Heryanto et al 2003, Walter et al 2005 to investigate the effects of E 2 on endometrial angiogenesis and VEGFA isoform and receptor expression in the uterus. Mice were bilaterally ovariectomised following anaesthesia with avertin (i.p.…”
Section: Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic mice were slightly older because tghFST315 mice do not demonstrate mating behaviour until ,8 wks of age (Lin et al 2008). Following bilateral ovariectomy, mice were left for a minimum of 7 days to recover and to allow for endometrial regression, before one of two steroid hormone protocols commenced (Heryanto and Rogers 2002;Walter et al 2005Walter et al , 2010Girling et al 2007). Protocol 1 (short-term oestrogen, E): mice were given a single subcutaneous (s.c.) injection of oestradiol-17b (100 ng in 100 mL peanut oil; Sigma-Aldrich, St Louis, MO, USA) or vehicle (100 mL peanut oil) 8 days post-ovariectomy (n Âź 7-9 per group).…”
Section: Study 1: Examination Of Fst Transgenic Oviducts and Uterimentioning
confidence: 99%